2008
DOI: 10.1007/s12011-008-8174-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Iron in Serum and Urine and their Relation with Thyroid Function in Female Goitrous Patients

Abstract: In many developing countries, women are at high risk of goiter and iron deficiency anemia (IDA). Iron deficiency adversely affects thyroid metabolism and may decrease the efficiency of thyroid hormones in areas of endemic goiter. The aim of the present study was to compare the level of iron (Fe) in biological samples (serum and urine) and serum thyroid hormones, thyroid stimulating hormone (TSH), free triiodothyronine (FT3), and free thyroxin (FT4) of goitrous female patients (GFPs; n = 69) with those of nongo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…In addition to proper nutrition, fluctuations in hormone levels may also act as a trigger in thyroid dysfunction, resulting in a sub-clinical thyroid imbalance in the body of both GMPs and GFPs. The consumption of a predominantly cereal-based diet, rich in phytate, oxalate, phosphate, and fiber enhance the Cu absorption which increases the Cu bioavailability, which was the main cause of Cu elevation in understudy patients [29]. It was reported that the phytic acid in humans inhibit absorption of Fe, I, Zn, calcium, magnesium, and manganese but not Cu [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to proper nutrition, fluctuations in hormone levels may also act as a trigger in thyroid dysfunction, resulting in a sub-clinical thyroid imbalance in the body of both GMPs and GFPs. The consumption of a predominantly cereal-based diet, rich in phytate, oxalate, phosphate, and fiber enhance the Cu absorption which increases the Cu bioavailability, which was the main cause of Cu elevation in understudy patients [29]. It was reported that the phytic acid in humans inhibit absorption of Fe, I, Zn, calcium, magnesium, and manganese but not Cu [30].…”
Section: Discussionmentioning
confidence: 99%
“…This is plausible because approximately 90% of ingested I is excreted in the urine whereas the remaining 10% is excreted in feces, however, with large inter-individual differences. Severe I deficiency may result in goiter [29] and cretinism. The results of our study substantiate growing concerns that dietary I deficiency is increasing in understudy area.…”
Section: Discussionmentioning
confidence: 99%
“…Parents were advised to follow it for at least 3 months. These foods were chosen because they are rich in the most important nutrients for thyroid: iron, vitamin A, and, to a lesser extent, iodine [13][14][15]24]. Table 1 shows the nutrients of …”
Section: Interventionmentioning
confidence: 99%
“…Several studies have been carried out examining the influence of specific nutrients on the thyroid, for example iron, iodine, and vitamin A [13][14][15]. These studies show that good iron, iodine, and vitamin A status are necessary for proper thyroid function.…”
Section: Introductionmentioning
confidence: 99%
“…Індекс КПВ у 12-річних дітей із дифузним нетоксичним зобом на момент початку зумовлює особливості йодного обміну та його зміни в різних геохімічних умовах [3, [5][6][7][8][9].…”
unclassified